Peningkatan Pengetahuan Masyarakat tentang Kesehatan Jiwa melalui Penyuluhan Kesehatan di Kelurahan Cibabat, Kota Cimahi - Rizky Gumilang Pahlawan; Septia Putri Hartanti; Zahra Laila Junistiani; Syipa Ananta Zahra; Desi Novitasari; Agustina Hermawanti; Turindah Turindah; Ahmad Adhi Karya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Mental health is an important aspect of overall well-being that influences how individuals think, behave, and interact with others. The increasing prevalence of mental disorders at both global and national levels indicates that mental health remains a significant public health concern. Limited public knowledge about mental health can hinder prevention, early detection, and proper management of mental disorders. This community service activity aimed to improve public knowledge and awareness regarding the importance of maintaining mental health. The activity was conducted on May 23, 2026, in Cibabat Village, North Cimahi District, involving 25 community members. Educational methods included lectures, discussions, question-and-answer sessions, and the use of supporting media such as leaflets and PowerPoint presentations. The results showed that participants were actively involved throughout the activity and demonstrated increased understanding of mental health concepts, risk factors, signs and symptoms of mental disorders, and prevention strategies. Continuous mental health education involving families and community members is recommended to strengthen awareness, enhance early detection, and support the promotion of mental well-being in the community.